Are lipid‐lowering drugs associated with a risk of cataract? A pharmacovigilance study. (17th July 2019) - Despas, Fabien; Rousseau, Vanessa; Lafaurie, Margaux; De Canecaude, Claire; Durrieu, Geneviève; Bagheri, Haleh; Montastruc, François; Montastruc, Jean‐Louis
Abstract: Some reports have raised concerns regarding a potential risk of cataracts associated with statins. However, clinical and observational studies evaluating the risk led to conflicting results. We assessed whether lipid‐lowering drugs (LLD) use is associated with an increased risk of cataract using the WHO's Individual Case Safety Reports database, VigiBase ® . We performed a disproportionality analysis with all reports between 1/1/1988 and 12/31/2018 to measure the reporting risk of 'cataract' in patients ≥45 years. Primary analysis compared LLD users to non‐users. To mitigate some potential confounding bias, we performed several sensitivity analyses excluding reports (i) with an association of at least two LLD, (ii) with antidiabetic and glucocorticoids and (iii) with lovastatin. We also analyzed the data according to the different classes of age limiting the period of study to years 2002–2012. We identified 14 664 reports of cataract (3 049 in LLD users, 66% women, 66 ± 20 years). Statins (84%, atorvastatin, simvastatin, rosuvastatin and lovastatin) were mostly reported, followed by fibrates (5.7%), nicotinic acid (3%), bile acid sequestrants (2%), herbal cholesterol and triglyceride reducers (2%) and others (ezetimibe, PCSK9 inhibitors, 15%). LLD users were associated with a greater risk of reports than non‐users (ROR 2.47, 95% CI 2.37–2.57). This association was also found for statins in general, fibrates, bile sequestrants, nicotinic acid, herbal drugs and others. Similar trends were observed in sensitivity analyses (except for fibrates and nicotinic acid after exclusion of reports with at least two LLD or in older patients ≥75 years). Using a large real‐life database (>18.5 million reports), we found a signal of cataract for LLD as a whole and statins, bile sequestrants and herbal drugs in particular. The signal disappeared for fibrates and nicotinic acid in older patients. No definite conclusions can be made for ezetimibe or PCSK9 inhibitors (evolocumab and alirocumab). This suggests that a decrease in cholesterol could be important in the pathophysiology of cataract in patients exposed to the main LLD.